Expansion of medical school admission quotas in Korea, is it really necessary? - Jeong Hun Park; Jungchan Lee; Kye-Hyun Kim; Yo Han Shin; Seog-Kyun Mun (BMC Public Health)
Abstract Background In 2024, the Korean Ministry of Health and Welfare enforced a policy to increase the number of medical school students by 2,000 over the next 5 years, despite opposition from doctors. This study aims to predict the trend of excess or shortage of medical personnel in Korea due to the policy of increasing the number of medical school students by 2035. Methods Data from multiple sources, including the Ministry of Health and Welfare, National Health Insurance Corporation, and the Korean Medical Association, were used to estimate supply and demand. The inflow-outflow method was used for supply estimation, and assumptions were made regarding national medical examination pass rates, clinical physician consultation rates, mortality rates, and overseas emigration rates. Per capita medical use by gender and age group in 2022 was calculated for demand estimation of future medical use, and the results of future population projections were applied. The numbers of working days examined were 265, 275, 285, and 289.5 days. Results The Korean government’s prediction that there will be a shortage of 10,000 doctors in 2035 can be confirmed by the underestimation of the number of working days (265 days). However, if the actual number of working days, 289.5 days, is applied, not only will there be no shortage of doctors in 2035, but there could also be an oversupply of 3,000 doctors. If the number of medical school students has increased for five years and the public’s medical use behavior and the number of working days for doctors are maintained at the current level, there is a possibility that there will be an oversupply of as many as 11,000 doctors by 2035. Conclusions Medical experts expressed concerns that the rapid increase in medical school enrollment would exacerbate the phenomenon of concentration, increase the cost of medical care, and collapse the medical system. In order to establish a reasonable plan for the supply and demand of medical personnel in the mid- to long-term, it is necessary to consider the future medical environment through discussions with medical providers and related organizations.